Rapid assessment of biochemical indicators of agronomic value in amaranth seed accessions from the VIR collection using NIR spectroscopy - T. V. Shelenga; A. E. Solovyeva; D. V. Sokolova; V. V. Vasipov; A. E. Smolenskaya; V. S. Popov (Труды по прикладной ботанике, генетике и селекции, 2025)
Background. Amaranth (Amaranthus L.) is a relatively new crop for the Russian Federation, with huge potential for growth intensity, productivity, and other agronomic traits. Development of new amaranth cultivars is an important solution to the problem of food quality improvement through the use of plant raw materials enriched with health-friendly and highly nutritious components. Calibration models were developed for rapid assessment of useful agronomic characters (the content of protein, oil, moisture, and basic fatty acids: palmitic, stearic, oleic, linoleic, and α-linolenic) in amaranth seeds preserved at the N.I. Vavilov All-Russian Institute of Plant Genetic Resources (VIR) using near-infrared (NIR) spectroscopy.Materials and methods. Thirty accessions of amaranth seeds (A. hypochondriacus L., A. cruentus L., and A. caudatus L.) from the VIR collection served as the material for the study. Biochemical indicators of seed quality and fatty acid composition of oil were studied using analytical methods adopted at VIR: the Kjeldahl method for protein content, the dry fat-free residue method for oil, the thermogravimetric method for moisture, and gas–liquid chromatography for fatty acid composition. Calibration models were constructed with the OPUS software developed for the MATRIX-I IR analyzer (Bruker Optics, Germany).Results and conclusion. Calibration models obtained on a MATRIX-I IR analyzer for measuring the content of protein, moisture, palmitic and oleic acids facilitate mass analysis of amaranth seeds from the VIR collection with an accuracy of 1.5%. Models developed for the quantification of oil, stearic, linoleic and α-linolenic acids require improvement. NIR spectroscopy makes it possible to accelerate the process of obtaining data on major agronomic indicators of amaranth seeds, preserve valuable materials, and determine further steps in breeding practice.